DAYA TARIK WISATA REKREASI ALAM MAYANG KOTA PEKANBARU - Hutabarat, Gita Nada Melodian; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Alam Mayang Recreation Tourism is one of the tourist attractions with outdoor recreation concept in Pecanbaru City. This research is intended to deyetermine attractiveness of Alam Mayang Recreation Tourism by using the theory of Bagyono, namely something to see, something to di, and something to buy This research uses a descriptive quantitative methods to examine the problems raised. The sample used was 100 people taken using Slovin formula. While the data collection techniques in this research used observation, documentation, and questionnaires using a Likert scale as a measurement tool. Based on the research results, the Alam Mayang Recreation Tourism get the grand total score is 3.204 in the score range of 2.719-3.359 in the good category, with the conclusion that the attraction of Alam Mayang Recreation Tourism is in the good category.Â Keywords : Attraction, Recreation, Alam Mayang.